Technology of Battery Grade Lithium Carbonate from domestic spodumene raw materials for lithium electrode materials - Nalibayeva, Arailym; Bishimbayeva, Gaukhar; Zhumabayeva, Dinara; Zhandayev, Nurlan; Bakenov, Zhumabay (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
Rapid development of the market for battery-powered devices, especially electric and hybrid cars and renewable energy over the past 10 years has led to a sharp demand for new high-capacity materials for LIB. Today, lithium is becoming a new strategic material capable of influencing the sustainable development of the world economy....
Keywords: lithium electrode materials; hybrid cars; renewable energy